Ungoverned spaces : alternatives to state authority in an era of softened sovereignty - Clunan, Anne L., 1968-; Trinkunas, Harold A. (Stanford Security Studies, 2010)
"Ungoverned spaces" are often cited as key threats to national and international security and are increasingly targeted by the international community for external interventions—both armed and otherwise. This book examines exactly when and how these spaces contribute to global insecurity, and it incorporates the many spaces where state authority is contested—from tribal, sectarian, or clan-based governance in such places as Pakistani Waziristan, to areas ruled by persistent insurgencies, such as Colombia, to nonphysical spaces, such … Show Moreas the internet and global finance. Within this multiplicity of contexts, the book addresses a range of security concerns, including weapons of mass destruction, migrants, dirty money, cyberdata, terrorists, drug lords, warlords, insurgents, radical Islamist groups, and human privacy and security.Ultimately, Ungoverned Spaces demonstrates that state-centric approaches to these concerns are unlikely to supplant the many sites of authority that provide governance in a world of softened sovereignty.